Quantum chemical research of the molecular structure of 3,4-dicyanofuroxan - I. N. Kolesnikova; N. V. Lobanov; V. N. Lobanov; I. F. Shishkov (Тонкие химические технологии)
Objectives. The study set out to determine the equilibrium parameters of the 3,4-dicyanofuroxan molecule by means of molecule geometry optimization by quantum chemistry methods, verify the adequacy of the methods used, and compare the obtained results with X-ray diffraction analysis (XRD) and gas electron diffraction (GED) data.Methods. Quantum chemical calculations were carried out using B3LYP, MP2, and CCSD(T) methods with 6-31G(d,p), cc-pVTZ, and aug-cc-pVTZ basis sets.Results. The equilibrium molecular structure of 3,4-dicyanofuroxan was refined by means of quantum chemical calculations using the Gaussian09 program. The geometrical parameters were compared with the structure of this compound in the solid phase and a number of related compounds in gas and solid phases. It was theoretically established that the planar equilibrium structure of the dicyanofuroxan molecule has CS symmetry. The structure of the free dicyanofuroxan molecule was found to differ depending on the phase. The B3LYP and CCSD(T) methods describe the molecular structure of dicyanofuroxan more accurately than the MP2 method. A regularity was revealed, according to which an increase in the basis, as a rule, leads to a better agreement of the geometry, regardless of the functional.Conclusions. The calculations performed are in good agreement with the literature data and results of joint analysis by GED and XRD. The effect of cyano substituents on the ring geometry is observed in comparison with the literature data for the dicyanofuroxan molecule. For the molecule in question, it is better to use the B3LYP/aug-cc-pVTZ method. The values of geometric parameters obtained by this method are in better agreement with the structure in the gas phase. The discrepancies with the experimental XRD results may be due to interactions in the crystal structure. Differences in the geometric parameters obtained on the basis of different functionals and bases make this molecule interesting for experimental structural studies using GED or microwave spectroscopy, which will permit the identification of optimal methods and bases for obtaining the geometric parameters of furoxan class molecules.